Preparação de membranas de acetato de celulose organomodificadas para adsorção dos íons Cu(II), Cd(II), Mn(II) e Ni(II) - Goveia, Danielle [UNESP]; Lobo, Fabiana Aparecida [UNESP]; Rodrigues Filho, Ubirajara Pereira; Dias Filho, Newton Luiz [UNESP]; Fraceto, Leonardo Fernandes; Rosa, André Henrique [UNESP] (Sociedade Brasileira de Química, 2010)
Cellulose acetate polymeric membranes had been prepared by a procedure of two steps, combining the method of phase inversion and the technique of hydrolysis-deposition. The first step was the preparation of the membrane, and together was organomodified with tetraethylortosilicate and 3-aminopropyltrietoxysilane. Parameters that exert influence in the complexation of the metallic ion, as pH, time of complexation, metal concentration, had been studied in laboratory using tests of metal removal. The membranes had presented resistance mechanics and reactivity to cations, being able to be an alternative for the removal, daily pay-concentration or in the study of the lability of metals complexed.
Preparation of the orgamomodified cellulose acetate membranes for adsorption of the ions Cu(II), Cd(II), Mn(II) and Ni(II)
Keywords: metals; cellulose acetate; organomodification